The Implementation of Differentiation Strategy and Its Effect on Customer Loyalty in the Indonesian Smartphone Industry: A Case Study of Mid-Tier Brands in Jakarta - Andi Rijaluddin Umar (Generasi Sains Indonesia, 2025)
The Indonesian smartphone industry has experienced rapid expansion, with mid-tier brands in Jakarta occupying a strategic position in serving consumers who demand affordability without sacrificing quality. Within this highly competitive environment, differentiation strategies are crucial for establishing brand distinctiveness and sustaining customer loyalty. This study investigates the application of differentiation strategies and their influence on customer loyalty among users of mid-tier smartphones in Jakarta. A quantitative survey approach was employed, complemented by semi-structured interviews and secondary data analysis. Data were collected from 150 respondents who had used mid-tier smartphones for a minimum of six months, ensuring informed evaluations. The findings indicate that product quality, features and innovation, brand image, and design significantly affect customer loyalty, with product quality emerging as the most influential factor. Conversely, after-sales service did not show a significant effect, suggesting that consumers in the mid-tier segment prioritize immediate functional value over long-term service considerations. Regression analysis reveals that differentiation strategies explain 63 percent of the variance in customer loyalty. These results highlight the importance of consistent quality management, continuous incremental innovation, and strong brand positioning globally.